ANALYSIS OF THE BITUMEN BINDING MODIFICATION SYSTEM FOR COLD PAINTING MIXTURES (CPMS) - Tilakov Sukhrob Mukhammadiyevich; Omondavlatov Ilkhom Bakhtiyor Ugli; Juraev Ilkhom Bekhmurodovich (European Science Publishing, 2026)
This article analyzes the modification methods used for binders in Cold Patch Mixes (CPMs) to enhance their strength and durability. The study examined the composition and mechanisms of action of traditional polymers such as Styrene-Butadiene-Styrene (SBS) and Styrene-Butadiene Rubber (SBR), as well as new composite modifications, including Microcapsules, Water-Soluble Epoxy Resin (WER), and Hybrid binders. The analysis demonstrates that modification significantly increases resistance to rutting at high temperatures and cracking at low temperatures, thereby extending the service life of CPMs in various weather conditions.
Keywords: Bitumen, modification, cold patch mixtures (CPMs), polymer bitumen, SBS, WER, hybrid binder, viscoelasticity, low temperature.